Frequency of unplanned surgery in patients with stage IV colorectal cancer receiving palliative chemotherapy with an intact primary: An analysis of SEER‐Medicare. Issue 3 (18th May 2019) - Lorimer, Patrick D.; Motz, Benjamin M.; Kirks, Russell C.; Han, Yimei; Symanowski, James T.; Hwang, Jimmy J.; Salo, Jonathan C.; Hill, Joshua S.
Abstract: Background and Objectives: Stage IV colorectal cancer is often treated with palliative chemotherapy with the primary tumor in place. Low rates of unplanned surgical intervention (due to obstruction or perforation) have been reported. We examined a large national dataset to determine the rate of unplanned surgical intervention in these patients. Methods: Surveillance Epidemiology and End Results‐Medicare were queried for patients with metastatic colorectal cancer receiving chemotherapy (1998‐2013). Patient who underwent planned surgery to the primary or metastasectomy were excluded. The primary outcome was the need for nonelective surgery. Time to surgery or death was measured. Conditional analyses were performed to determine the risk of surgical intervention at 6‐month, 1‐, and 2‐year after diagnosis. Results: The analytic cohort consisted of 4692 patients (median age = 75). At 24 months, 80% of the patients had died. The overall unplanned intervention rate was 12%. The probability of requiring unplanned surgery between 6 and 12 months was 8.1%; 12 and 24 months = 6.7%, and >24 months = 5.3%. Males, those with right‐sided tumors, and older patients were less likely to require surgery. Conclusions: Patients treated with palliative chemotherapy who are not resected upfront are unlikely to require unplanned surgery. Prophylactic surgery to reduce the risk of perforation or obstruction may not be necessary.